2017
DOI: 10.1177/1071100717732723
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Outcomes Between Step-Cut Lengthening Calcaneal Osteotomy vs Traditional Evans Osteotomy for Stage IIB Adult-Acquired Flatfoot Deformity

Abstract: Level III, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
(44 reference statements)
3
26
0
Order By: Relevance
“…The existing literature shows that increased pressure on the CC joint is a well-documented complication after E-LLCOT, even if a standard graft size is used. 7,8,20 In addition, we detected 1 (5.8%) case of subluxation of the CC joint following E-LLCOT, which is reported to be a major risk factor for E-LLCOT and can also lead to CC-arthritis. 5,6,14,22,23 There was no subluxation of the CC joint after H-LLCOT.…”
Section: Discussionmentioning
confidence: 71%
“…The existing literature shows that increased pressure on the CC joint is a well-documented complication after E-LLCOT, even if a standard graft size is used. 7,8,20 In addition, we detected 1 (5.8%) case of subluxation of the CC joint following E-LLCOT, which is reported to be a major risk factor for E-LLCOT and can also lead to CC-arthritis. 5,6,14,22,23 There was no subluxation of the CC joint after H-LLCOT.…”
Section: Discussionmentioning
confidence: 71%
“…34,116 Preliminary work has shown that patients who undergo this osteotomy have excellent healing and correction with few of the complications inherent to traditional LCL, although there is a risk of peroneal tendon injury due to the proximal osteotomy. 34,104…”
Section: Forefoot Abductionmentioning
confidence: 99%
“…12,24,27 Because LCL is a powerful procedure in correcting abduction and there is a risk for overcorrection, studies have cited a TN uncoverage of greater than 40% as an indication for LCL. 9,24 Previous work has also derived a linear equation relating the change in lateral incongruency angle (LIA) with the amount of LCL correction, 3 which allows for preoperative planning and titration of operative correction. 6 Proper titration and correction are integral to the success of the procedure as multiple studies have shown that overcorrection (adduction of the TN joint) is associated with inferior patient-reported outcomes in addition to lateral column overload, increased risk for stress fractures of the fifth metatarsal, increased lateral plantar pressure, and pain.…”
Section: Rationalementioning
confidence: 99%